Metode dan Model Pembelajaran Sejarah Kebudayaan Islam - Amalia Syurgawi; Muhammad Yusuf (Maharot : Journal of Islamic Education, 2020)
This paper aims to determine the learning model of the history of Islamic education (SKI), this paper is a literature review using the descriptive qualitative method. From the results of the author's search, it shows that the history of Islamic culture is a subject that is directed to understand and recognize Islamic history. The methods used in studying Islamic history are the lecture method, question and answer, discussion, demonstration, timeline, concept map, role playing, active knowledge sharing. Furthermore, the factors that need to be considered in learning are objectives, audiences, facilities, strengths and weaknesses. The implication of this journal is that the readers can understand the methods in teaching the history of Islamic culture.